1988
DOI: 10.2307/1241987
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Intrahousehold Allocation of Food in the Rural Philippines

Abstract: This study shows that the opportunity cost of time for husbands and wives can affect the intrahousehold distribution of food in a developing country. Equations which explain the relative allocation of calories within households were estimated for husbands, wives, and children with data for the rural Philippines. The estimating equation is derivable from both a joint household utility function a n d a bargaining model. Because the same households were included in the four survey rounds, the various observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 6 publications
2
31
1
1
Order By: Relevance
“…As a result, female children are likely to be in a disadvantageous position for nutrient intakes. The favouring of boys in the intra-household distribution of nutrients is consistent with the findings of the previous studies in China (Senauer et al 1988;Lee 2011).…”
Section: Effect Of Migration On the Nutrition Intakes Of Childrensupporting
confidence: 91%
“…As a result, female children are likely to be in a disadvantageous position for nutrient intakes. The favouring of boys in the intra-household distribution of nutrients is consistent with the findings of the previous studies in China (Senauer et al 1988;Lee 2011).…”
Section: Effect Of Migration On the Nutrition Intakes Of Childrensupporting
confidence: 91%
“…The circumstantial evidence for the existence of pro-male bias has been documented widely. In numerous studies, boys are found to have better school outcomes (Behrman, Pollak, and Taubman 1982;Deolalikar 1993;Davies and Zhang 1995;Nkamleu and Kielland 2006) or to have better health outcomes (Rosenzweig and Schultz 1982;Bairagi 1986;Das Gupta 1987;Rosenzweig and Wolpin 1988;Senauer, Garcia, and Jacinto 1988). However, finding evidence of actual pro-male bias in intrahousehold resource allocation has been more elusive (Kingdon 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of income effects on household welfare show that female income provides an advantage (Senauer, Garcia, and Jacinto 1988;Thomas 1990;Brown, Yohannes, and Webb 1994). Refinements of this type of study have examined the "lumpiness" of income to show that food expenditures depend on gender-disaggregated seasonal income flows (Hopkins, Levin, and Haddad 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Behrman also contends that, compared to research in the United States, those in developing countries are less likely to exhibit "inequality aversion"-the act of compensating for child deficiencies with an increased allocation of resources. According to other research [18], the pro-male bias in allocation is also age specific. Adult males are the most preferred, followed by older male children, younger male children and then the women in the household in that order.…”
Section: Data Were Obtained From the 2007-2008 National Health And Numentioning
confidence: 86%